2020
DOI: 10.1177/0025802420934241
|View full text |Cite
|
Sign up to set email alerts
|

The Islamic perspective on physician-assisted suicide and euthanasia

Abstract: Physician-assisted suicide (PAS) and euthanasia can be debated from ethical and legal perspectives, and there are a variety of views regarding their acceptability and usefulness. Religion is considered an important factor in determining attitudes towards such practices. This narrative review aims to provide an overview of the Islamic perspective on PAS and euthanasia and explore the Islamic approach in addressing the related issues. The PubMed database was searched to retrieve relevant articles, then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…According to religious principles in Iran, humans do not have the right to decide to die, and euthanasia is highly ignored and against the law. 10, [45][46][47] This view is also supported in other Islamic countries, such as Singapore, 48 Pakistan, 49 Indonesia, 49 and Turkey. 7 It is evident that the level of education, the type of religion, and religiosity of individuals have a significant impact on nurses' overall attitudes toward euthanasia.…”
Section: Discussionmentioning
confidence: 86%
“…According to religious principles in Iran, humans do not have the right to decide to die, and euthanasia is highly ignored and against the law. 10, [45][46][47] This view is also supported in other Islamic countries, such as Singapore, 48 Pakistan, 49 Indonesia, 49 and Turkey. 7 It is evident that the level of education, the type of religion, and religiosity of individuals have a significant impact on nurses' overall attitudes toward euthanasia.…”
Section: Discussionmentioning
confidence: 86%
“…Finally, religiosity was negatively correlated with approval of euthanasia in specific cases. There is a long-standing condemnation of most or all forms of assisted dying in several global religious traditions, including Orthodox Judaism ( Bradley, 2009 ), Christianity ( Baeke et al, 2011 ), and Islam ( Madadin et al, 2020 ). A recent systematic review of attitudes towards PAS across five world religions found largely negative attitudes in Islamic respondents, variable responses in Christian and Jewish respondents, and limited acceptance in Buddhist respondents.…”
Section: Paradoxical Correlates Of Attitudes Towards Pas: Analyzing the Results Of The World Values Surveymentioning
confidence: 99%
“…Further searches were conducted within these results using the additional search terms "caregiver," "caregiver burden," "stress," "behavioral and psychological symptoms of dementia," "BPSD," "economic," "financial," "autonomy," "dignity," "identity," "personhood" and "ethics." By this method, a total of 103 citations were retained (Pereira, 2011;Schuurmans et al, 2021;Kemmelmeier et al, 2002;Bradley, 2009;Baeke et al, 2011;Chakraborty et al, 2017;Madadin et al, 2020;Nichols, 2013;Emanuel et al, 2000;Krag, 2014;Trachtenberg and Manns, 2017;Bilchik, 1996;Lazar and Davenport, 2018;Karrer et al, 2020;Stakišaitis et al, 2019;Finucane et al, 2007;Finucane, 1999;Sachs et al, 2004;Dominguez et al, 2021;Meier, 1997;Liu et al, 2020;Gao et al, 2019;Gilhooly et al, 2016;Watson et al, 2019;Cheng, 2017;Biggs et al, 2019;Fam et al, 2019;Dening et al, 2013;Owen et al, 2001;Cohen-Mansfield and Brill, 2020;Anderson et al, 2019;O'Dwyer et al, 2016;Bravo et al, 2018;Wicher and Meeker, 2012;Stolz et al, 2015;Seike et al, 2021;Kashimura et al, 2021;Zwingmann et al, 2018;…”
Section: Pitfalls Inherent In the Practice Of Pas In The Specific Case Of Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…Islamic countries, like Iran, do not have laws permitting euthanasia. Hence, performing any kind of euthanasia by the physician, even after getting the patient’s consent, is considered a murder ( Madadin et al, 2020 ). As a result, to avoid future legal and criminal issues, comprehensive interventions are needed to change medical staff’s attitudes toward passive euthanasia in Iran during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%